2023
DOI: 10.1021/acsaem.2c03587
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Evolution Reaction by Silicate-Stabilized Manganese Oxide

Abstract: Oxygen evolution reaction (OER) through water oxidation under acidic conditions catalyzed by first-row transitionmetal-based compounds remains a challenge in artificial photosynthesis. A critical issue for OER under acidic conditions is the solubility of first-row transition-metal compounds during the reaction. This study investigates the silicate-stabilized Mn oxide for OER under acidic conditions (H 2 SO 4 (0.10 M)). Compared to Mn oxide, the silicate-stabilized Mn oxide is significantly more stable under ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…These metals are more affordable, which facilitates their use in industrial conditions. Still, one should also be aware of the stability of these transition-metal-based electrocatalysts, which, in acidic conditions, is generally low (Goberna-Ferrón et al, 2015;Sun et al, 2015;Lu et al, 2019;Zand et al, 2023), hence why there are fewer studies on this type of media.…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
See 1 more Smart Citation
“…These metals are more affordable, which facilitates their use in industrial conditions. Still, one should also be aware of the stability of these transition-metal-based electrocatalysts, which, in acidic conditions, is generally low (Goberna-Ferrón et al, 2015;Sun et al, 2015;Lu et al, 2019;Zand et al, 2023), hence why there are fewer studies on this type of media.…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
“…The results showed that the catalytic activity was less than optimal since the overpotential needed to achieve 10 mA/cm 2 was 640 mV, and the OER onset potential was 1.757 V vs RHE. On the other hand, the stability was greatly improved because the modified Mn oxide showed higher current retention and virtually no structural changes after OER (Zand et al, 2023).…”
Section: Frontiers In Energy Researchmentioning
confidence: 99%
“…For example, phase conversions were observed for metal (hydr)oxides during the OER while many Mn oxides (Mn 3 O 4 , α-Mn 2 O 3 , β-MnO 2 , CaMnO 3 , Ca 2 Mn 3 O 8 , CaMn 3 O 6 , and CaMn 4 O 8 ) convert to layered Mn oxide in the presence of CAN and during the OER, where layered Mn oxide is an efficient OER catalyst. 6…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, developing efficient and stable oxygen-evolution catalysts (OECs) is crucial to yield breakthroughs in water-splitting technology. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Mn, [4][5][6][7][8][9][10] Fe, [11][12][13][14][15] Co, [16][17][18] Ni, [19][20][21] and Cu 22,23 compounds are synthesized using different methods and applied as OECs. Among other conditions, the oxygen-evolution reaction (OER) in the presence of cerium(IV) ammonium nitrate (CAN) as a sacrificial oxidant has been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation